Ecological footprint and human well-being nexus: Accounting for broad-based financial development, globalization, and natural resources in the Next-11 countries - Solomon Prince Nathaniel (Future Business Journal, 2021)
The Next-11 (N11) countries have witnessed great advancements in economic activities in the past few years. However, the simultaneous attainment of environmental sustainability and improved human well-being has remained elusive. This study probes into ecological footprint (EF) and human well-being nexus in N11 countries by applying advanced estimation techniques compatible with heterogeneity, endogeneity, and cross-sectional dependence across country groups. From the findings, human well-being, captured by the human development index, increases the EF, and EF also increases human well-being which suggests a strong trade-off between both indicators. This shows that policies that are channeled toward promoting human well-being are not in consonance with environmental wellness. Financial development and biocapacity increase the EF, while natural resources and globalization reduce it. Human well-being increases the EF in all the countries except in Egypt. This study argues that strong institutions could help mitigate the trade-offs and ease the simultaneous attainment of both environmental preservation and improved human well-being. The limitations of the study, as well as, possible directions for future research are discussed.
Keywords: 650; AMG; Ecological footprint; Financial development; Globalization; Human well-being; Sustainable development